2010
DOI: 10.1088/1757-899x/7/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

The role of SIMS in the investigation of the complex crystal chemistry of mica minerals

Abstract: A full characterisation of micas requires complete chemical analysis, including the determination of light elements, combined with Mössbauer spectroscopy or any technique suitable for the determination of ferric and ferrous iron contents, and crystal structural analysis (SCXRD). In this context, the SIMS technique is essential for a deeper understanding of the crystal chemistry of mica owing to its capability of precise and accurate quantification of light elements, i.e., H, Li, B, F, .... The role of SIMS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The mean SIMS values for the H 2 O and Li contents are utilized here: H 2 O = 0.64 (8) wt%; Li 2 O = 0.027 (1) wt%. For the SIMS measurements of fluorine, Ottolini et al (2010) found an average concentration of F = 6.3 (8) wt%, whereas F EPMA in samples from the present work is in the range 3.4-4.1 wt% (see Table 1). For a discussion on the causes of discrepancies relevant to fluorine data between EPMA and SIMS see Ottolini et al (2000), Bellatreccia et al (2006), and Scordari et al (2008).…”
Section: Chemical Analysessupporting
confidence: 46%
See 3 more Smart Citations
“…The mean SIMS values for the H 2 O and Li contents are utilized here: H 2 O = 0.64 (8) wt%; Li 2 O = 0.027 (1) wt%. For the SIMS measurements of fluorine, Ottolini et al (2010) found an average concentration of F = 6.3 (8) wt%, whereas F EPMA in samples from the present work is in the range 3.4-4.1 wt% (see Table 1). For a discussion on the causes of discrepancies relevant to fluorine data between EPMA and SIMS see Ottolini et al (2000), Bellatreccia et al (2006), and Scordari et al (2008).…”
Section: Chemical Analysessupporting
confidence: 46%
“…However, Ottolini et al (2010) produced SIMS analyses on three crystals of the Ma1-series different from those considered here, but separated from the same rock sample. The mean SIMS values for the H 2 O and Li contents are utilized here: H 2 O = 0.64 (8) wt%; Li 2 O = 0.027 (1) wt%.…”
Section: Chemical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversion from X-ray counts to oxide weight percentages (wt%) was obtained with the PAP data reduction method (Pouchou and Pichoir 1985). Chemical compositions are reported in Table 2, where atomic proportions are calculated on the basis of 12(O, OH, Cl, F) and by combining EMPA data with those of Mössbauer spectroscopy (Scordari et al 2006) and SIMS measurements (Ottolini et al 2009). The final formulae were obtained by allowing H 2 O variations within 1-2 estimated standard deviations (e.s.d.)…”
Section: Electron Microprobe Analysesmentioning
confidence: 99%